Women in sexuality education: The impact of the Irish Family Planning Association's WiSE UP Programme - Pembroke, Sinead (Crisis Pregnancy Agency, 2007)
There has been a long-standing gap in effective education on sex and sexuality in Ireland at the levels of both schools and communities. Of particular concern is the lack of access to good quality education for people living in communities affected by social exclusion. WiSE UP is a pilot programme on sexuality education designed by the Irish Family Planning Association (IFPA) for women living and working in communities experiencing social exclusion. It was developed to respond to two complex dimensions in Irish society: the need for a policy response to sex, sexual health and sexuality education for adults and the need for a skills base about sex and sexuality within communities experiencing social exclusion.
Keywords: Social exclusion; Sexuality education; WiSE UP; Irish Family Planning Association (IFPA); Inclusive Society